INVESTIGATIONS OF ANTIMICROBIAL AND PHYTOCHEMICAL ANALYSIS OF ARGEMONE MEXICANA MEDICINAL PLANT EXTRACTS AGAINST BACTERIA WITH GASTROINTESTINAL RELEVANCE - Veni T; T, Pushpanathan (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The objective of the study was to evaluate antibacterial potential and phytochemical analysis of various extracts of Argemone Mexicana. Methods: The antimicrobial activity of various extracts of A. Mexicana were analysed by using agar well disc diffusion method. Results: The ethanolic and methanolic extracst of A. mexicana had showed significant antimicrobial activity. Similar result was not observed in other four extracts. The higher content of reducing sugar, flavanoids, tannin, sterol, terpene and alkaloid were found in all the extracts of A. Mexicana are comparable with Amoxicillin. Conclusion: The results obtained from this study indicate that A. mexicana is a potential source of antimicrobial and thus could prevent many diseases. Â Keywords: A. mexicana, Antimicrobial activity, Phytochemical analysis, Infectious diseases, Medicinal plants and Plant extract.